Residual Herbicide Effect on Interseeded Annual Clover in Southern Forage Systems. (11th May 2018) - Tucker, Jennifer J.; Mullenix, M. Kimberly; Enloe, Stephen F.; Burch, Pat L.
Abstract: Across the southeastern United States, pyridine carboxylic acid herbicides are widely used for broadleaf weed control in permanent grass pastures. This family of herbicides has proved very successful for controlling most broadleaf weeds commonly present in southeastern pastures and hayfields. In the southern United States, producers have expressed concern when overseeding legume species into warm-season perennial sods following application of commonly used pyridine carboxylic acid herbicides, as legumes are generally highly sensitive to this herbicide family. Field experiments were established to evaluate two herbicide treatment programs (residual vs nonresidual) on crimson clover overseeded into bermudagrass sod. The residual herbicide program included aminopyralid plus 2, 4-D (0.09 + 0.7 kg ae ha –1 ), and the nonresidual program included triclopyr plus fluroxypyr (0.63 + 0.21 kg ae ha –1 ) plus 2, 4-D (1.12 kg ae ha –1 ). Herbicide programs were applied at two key timings: in spring (May) and early summer (June). Spring applications were also evaluated when used in single vs repeated annual application. Our results did not indicate soil residual herbicide issues for crimson clover planted in the fall following spring or early-summer application of aminopyralid + 2, 4-D at either location. Additionally, there were no cumulative negative impacts on crimson clover following 2 yr of spring herbicide application. Crimson clover cover, however, strongly decreased as grass and weed cover increased––an event that may be related to greater interspecific competition at higher levels of grass and weed cover. Soil fertility, weather, and competition from resident annual grasses and weeds strongly influenced productivity, suggesting that changes in pasture dynamics had a greater influence on clover productivity than did herbicide treatment or timing of application.